2008
DOI: 10.5641/193250308x13086753542771
|View full text |Cite
|
Sign up to set email alerts
|

Walking for Health in Pregnancy: Assessment by Indirect Calorimetry and Accelerometry

Abstract: The purpose of this study was to examine RT3 accelerometer activity counts and activity energy expenditure of 36 pregnant women at 20 and 32 weeks' gestation during treadmill walking and free-living conditions. During treadmill walking, oxygen consumption was collected, and activity energy expenditure was estimated for a 30-min walk at a self-selected walking pace. The number of min it would take a pregnant woman to meet exercise recommendations (i.e., kcal/week) were calculated. Preliminary activity count cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…This decrease comes from reductions in both movement intensity and the duration of physical activity (21,(23)(24)(25). Furthermore, in studies of well-nourished, normal-weight pregnant women, there is a decrease in the measured speed of SSW from early to late (26) and mid to late (27) gestation. Little objective data are available on the degree to which SSW speed or walking economy changes in obese women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease comes from reductions in both movement intensity and the duration of physical activity (21,(23)(24)(25). Furthermore, in studies of well-nourished, normal-weight pregnant women, there is a decrease in the measured speed of SSW from early to late (26) and mid to late (27) gestation. Little objective data are available on the degree to which SSW speed or walking economy changes in obese women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, each method has its own strengths and limitations. The RT3 accelerometer is used to assess physical activity in children [10,11], adolescents [11], overweight adults [12], pregnant women [13], individuals with multiple sclerosis [14], and older adults with coronary heart disease [15]. Klassen et al report that the RT3 accelerometer can detect a significant difference between moderately active and active individuals with multiple sclerosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although its reliability, validation, and application in measuring physical activeity in different population have been reported [10][11][12][13][14][15], the relationship between disease activity and energy expenditure measured by the RT3 accelerometer in SLE patients has not been previously established.…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum factors associated with inactivity included weight retention, working longer hours in the first trimester and reported lack of child care. Dinallo et al 35 used accelerometry to show that pregnant women slowed down their walking pace in a treadmill walking condition as pregnancy progressed. The authors observed that less than 12% of women in the study's free-living condition met recommended physical activity guidelines consistent with the findings of other investigations.…”
Section: Influence Of Physical Activity In Pregnancymentioning
confidence: 99%